An Indolocarbazole‐Based Thermally Activated Delayed Fluorescence Host for Solution‐Processed Phosphorescent Tandem Organic Light‐Emitting Devices Exhibiting Extremely Small Efficiency Roll‐Off. (20th January 2019) - Ohisa, Satoru; Takahashi, Tatsuya; Igarashi, Masahiro; Fukuda, Hitoshi; Hikichi, Tatsuya; Komatsu, Ryutaro; Ueki, Emi; Pu, Yong‐Jin; Chiba, Takayuki; Kido, Junji
Abstract: The study reports the development of a solution‐processed phosphorescent tandem organic light‐emitting device (OLED) exhibiting extremely small efficiency roll‐off. The OLED comprises two light‐emitting units (LEUs) connected by an interconnecting unit and employs a thermally activated delayed fluorescence host material. One of the most difficult tasks in the fabrication of OLEDs is to form a multilayer structure without dissolving the underlayer during the coating of the upper layer. The developed host materials exhibit high tolerance to methanol. The upper‐layer adjacent to the light‐emitting layer consists of ZnO nanoparticles, which could be dispersed in methanol by improving the preparation method. This results in the successful fabrication of a solution‐processed phosphorescent tandem OLED comprising two LEUs. The maximum external quantum efficiency (EQE) of the tandem device is 22.8%, and the EQE is 21.9% even at a high luminance of 10 000 cd m −2 . The suppression of efficiency roll‐off is among the best of those previously reported. Moreover, the operational stability of the tandem device is much higher compared with single‐LEU devices. Abstract : An indolocarbazole‐based thermally activated delayed fluorescence host is developed for solution‐processed phosphorescent tandem organic light‐emitting devices exhibiting extremely small efficiency roll‐off. The maximum external quantum efficiency (EQE) of the tandem device is 22.8%, and the EQE is 21.9% even at a high luminance of 10 000 cd m −2 . The suppression of efficiency roll‐off is among the best of those previously reported.